Communication in Responsible Business - Conaway, Roger N (Business Expert Press, 2012)
Ebook from IG Library ; Stakeholders today want to know about your company’s social and environmental performance. Effectively communicating these topics has become critical to economic success. This book offers an extensive toolbox of the most effective instruments that can help you, and each chapter provides specific examples of how to communicate social and cause-related marketing, sustainability reporting, issues and crisis communication, vision, mission statements and codes, and web-based stakeholder communication. You will find hands-on concepts and actual illustrations. Chapter cases provide rich practical coverage and translate concepts into solutions for dayto-day business realities.